What is changed in HBV molecular epidemiology in Italy?. Issue 5 (5th February 2018) - Lai, Alessia; Sagnelli, Caterina; Lo Presti, Alessandra; Cella, Eleonora; Angeletti, Silvia; Spoto, Silvia; Costantino, Sebastiano; Sagnelli, Evangelista; Ciccozzi, Massimo
Abstract : Hepatitis B virus (HBV) infection represents the most common cause of chronic liver diseases worldwide. Consequently, to the introduction of the universal HBV vaccination program, the prevalence of hepatitis B surface antigen was markedly reduced and less than 1% of the population of Western Europe and North America is chronically infected. To date, despite great advances in therapeutics, HBV chronic infection is considered an incurable disease. Ten hepatitis B virus genotypes (A‐J) and several subgenotypes have been identified so far, based on intergroup divergences of 8% and 4%, respectively, in the complete viral genome. HBV‐D genotype has been found throughout the world, with highest prevalence in the Mediterranean area. In the present review, several articles concerning HBV epidemiology, and phylogeny in Italy have been analyzed, mainly focusing on the changes occurred in the last decade.